Design optimization methodology of submarine using multilevel numerical CFD models - Mohamad Barhm; Amroune Salah; Miri Rached; Benchekkour Abdellah; Galoyan Karlen (FME Transactions)
This study explores the hydrodynamic and aerodynamic performance of a submarine and an airfoil under various angles of attack (AoA) using advanced computational fluid dynamics (CFD) simulations. The incompressible Reynolds Averaged Navier-Stokes (RANS) equations were solved using ANSYS, leveraging its segregated flow solver and adjoint optimization capabilities to automate the creation and meshing of computational domains. By analyzing velocity and pressure distributions across coarse and fine mesh resolutions, the research highlights the superior accuracy of fine meshes in capturing complex flow phenomena, such as flow separation, wake behavior, and velocity gradients. Submarine simulations with control surfaces revealed distinct symmetries and nearly zero maneuvering coefficients for specific configurations, filling gaps in the existing literature on fully appended geometries. Optimization efforts led to an enhanced design with improved aerodynamic efficiency, achieving reduced drag and stabilized flow, as validated by consistent performance at AoAs of 0°, 20°, and 80°. This work demonstrates the importance of fine mesh resolution, automated workflows, and adjoint solvers in accelerating the iterative design process and optimizing marine and aerodynamic structures for real-world applications. These findings highlight the significant influence of high attack angles on the submarine's vertical plane flow. Such insights offer a mechanical foundation for analyzing nonlinear motion phenomena during submarine surfacing.